READ-ing antimicrobial stewardship in the Caribbean: a tri-nation document review - Tamarie Rocke; Aniebiot-abasi Udofia; Nathalie El Omeiri; Pilar Ramon-Pardo (Pan American Health Organization, 2023)
Objective. To explore the antimicrobial stewardship policy landscape in three English-speaking Caribbean countries (Barbados, Guyana, and Saint Lucia) and examine the key enablers and challenges to the design and implementation of formal antimicrobial stewardship programs. Methods. A document analysis that searched for existing policy, communications, and contributions on antimicrobial stewardship from these three countries, adapting the READ (Ready materials; Extract data; Analyze data; Distill findings) approach, a systematic procedure for health policy document review. Results. The search strategy identified 726 initial records. Of those, 15 (2%) met the inclusion criteria. The analysis included official policy documents (n = 3), scholarly works/reviews (n = 3), advocacy documents (n = 2), news articles (n = 4), and confidential reports (n = 3) from the three countries. Conclusions. Critical matters such as cross-programmatic coordination, the significance of individual action, and the need for bidirectional knowledge discourse are prominent in optimizing antimicrobial stewardship adaptation in these countries. CARICOM regional coordination has positively impacted the integration of infection prevention and control with antimicrobial stewardship across this knowledge network.